Penerapan Teknologi Pestisida Nabati Limbah Tembakau di Kelompok Tani Harapan Desa Slateng, Ledokombo, Jember Lereng Gunung Raung Mendukung Green Economy - Tanzil, Ahmad Ilham; Basuki, Basuki; Widjayanti, Fwfi Nurdiana (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Jember is one of the districts located in the horseshoe area of East Java Province. Jember Regency is a tobacco-producing area that is later processed into raw material for cigars and kretek cigarettes. However, harvest waste is often not utilized optimally, thereby polluting the environment. Through assistance from the Harapan farmer group in Slateng Village, Ledokombo District, and Jember, tobacco waste can be processed into vegetable pesticides that can control and prevent the appearance of insect pests in cultivated plants. Service activities began with surveys with partners, outreach regarding the benefits of tobacco waste, training in making vegetable pesticides, and application on land. Based on the results of the training and the application of the plant-based pesticides that were made, the community was satisfied because they could control insect pests because the tobacco and rice poison was contact in nature.